1976
DOI: 10.1139/e76-082
|View full text |Cite
|
Sign up to set email alerts
|

Large scale magnetic anomalies over western Canada and the Arctic: a discussion

Abstract: A conroured map of vertical magnetic held residuajs (relative to the IGRF) over western Canada and adjacent Arctic regions has been produced by amalgamating new data with those from previous surveys. The measurements were made at altitudes between 3.5 and 5.5 km above sea level. The map shows the form of the magnetic field within the waveband 30 lo 5000 km. A magnetic feature of several thousand LiIomerres wavelength dominates the map. and is probably due in major part to sources in the earth's core. Superimpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 36 publications
(60 reference statements)
1
17
0
Order By: Relevance
“…On regional scale compilations, such as the magnetic anomaly map of North America (Geological Society of America, 1987), this anomaly is revealed as a large positive feature. Coles et al (1976) also confirmed the presence of this Magsat anomaly from high-level airborne data. They described it as a wide belt of intense anomalies that may be evidence for a Precambrian orogenic zone.…”
Section: Magnetic Anomaliessupporting
confidence: 73%
See 1 more Smart Citation
“…On regional scale compilations, such as the magnetic anomaly map of North America (Geological Society of America, 1987), this anomaly is revealed as a large positive feature. Coles et al (1976) also confirmed the presence of this Magsat anomaly from high-level airborne data. They described it as a wide belt of intense anomalies that may be evidence for a Precambrian orogenic zone.…”
Section: Magnetic Anomaliessupporting
confidence: 73%
“…They described it as a wide belt of intense anomalies that may be evidence for a Precambrian orogenic zone. Coles et al (1976) further suggested that the crystalline continental basement (Fig. 3, Interior Platform) extends far to the west beyond the exposed and known buried shield.…”
Section: Magnetic Anomaliesmentioning
confidence: 95%
“…They unconformably overlie and intrude rocks deformed and metamorphosed during the Calderian orogeny . The zone can be traced along strike for an additional 500 km southward beneath a thin veneer of Paleozoic cover and to the north bends westward then continues for another 300 km (Coles et al, 1976;Hildebrand and Bowring, 1984;Hoffman, 1987;Hildebrand et al, 2010). Thus, its two-dimensional extent is comparable to modern continental arc terranes.…”
Section: Great Bear Magmatic Zonementioning
confidence: 90%
“…Geological interpretations of the data shown in Fig. 3 are given in Haines et al (1971) and Coles et al (1976Coles et al ( , 1981. The data have been reduced to magnetic anomalies using the appropriate Definitive Geomagnetic Reference Field (DGRF) (Langel 1992), which provide an improved regional field representaCan.…”
Section: Earth Physics Branch Datamentioning
confidence: 99%